Students' Perceptions in Using WhatsApp as Learning Media - Priskila Novianti; Tri Kurniawati; M.Iqbal Ripo Putra; Ageung Darajat (XXXX-XXXX, 2022)
This research aimed to find out students’ perceptions in using WhatsApp as learning media to the Eleventh Grade students of SMA Negeri 1 Suti Semarang in the Academic Year of 2020/2021. This research was descriptive survey design in quantitative describe method. The participants of this research were 30 students. The proposed research applied online questionnaire (close-ended) as a tool. The closed-ended questionnaire was modified instrument based on Embi (2016) which consisted 20 statements rated four Likert-scale. To help researcher calculating the data and managing the charts, the researcher operate Ms. Excel 2016 to measurement of frequenc and percentage of the data. The findings stated that almost all students had positive perceptions on the use of WhatsApp as learning media. The findings indicated that almost all of aspects of WhatsApp were averaged at agreed scale. The findings also indicated that WhatsApp is helpfull, useful, and flexible to support students learning activities, however to access the internet in online learning is still expensive. Therefore, from the explained above the researcher conclude that, WhatsApp is a media that can be used to support learning process especially in the school.